PENGARUH WORD OF MOUTH (WOM) DAN PROMOSI TERHADAP MINAT MENONTON FILM INDONESIA PADA BIOSKOP DI KOTA KARAWANG - Setiawati, Widya; Kosasih, Kosasih; Ratnasari, Ina (Faculty of economcs Universitas Singaperbangsa Karawang, 2022)
The research was conducted using descriptive and verification methods, namely collecting, presenting, analyzing, and testing hypotheses, as well as making conclusions and suggestions. A sample of 221 respondents from a population of 88062 viewers and processed using SPSS25. The results of this study are in the agreed criteria and are good in all variables. The correlation coefficient between the independent and independent variables has a strong and direct correlation level because the value is positive and has a significant correlation. Word of Mouth contributes less to Interests than Promotions. The results of the analysis of the simultaneous influence of Word of Mouth and Promotion on Interest 37.9%, with sig criteria then H0 is rejected because it is said that Word of Mouth and Promotion have a significant influence on Interest. While the remaining 66.2% is the contribution of other variables (ɛ) which were not examined in this study.